2021
DOI: 10.3389/fmars.2021.575866
|View full text |Cite
|
Sign up to set email alerts
|

Whale-Watching Management: Assessment of Sustainable Governance in Uramba Bahía Málaga National Natural Park, Valle del Cauca

Abstract: As the growth of the whale-watching activity increases rapidly around the world, the challenge of responsible management and sustainability also rises. Without suitable management, operators may try to maximize their own profits by breaking the rules, which may negatively affect cetaceans. In this paper, the applicability of conditions for sustainability governance in humpback whale-watching was evaluated. To achieve this purpose, semi-structured interviews were conducted in Uramba Bahía Málaga National Natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A recent published study showed that for 2015, humpback whale-watching activity in Bahía Málaga met only 16% of the conditions for sustainable governance, and it was characterized by unevenness in connections with markets (i.e. price variability and connections with intermediaries), income inequality, the lack of a whalewatching operators' association, and the lack of support from government organizations (Soto-Cortés et al, 2021). Therefore, we encourage the environmental authorities and local people to facilitate the formation of an association.…”
Section: Social Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent published study showed that for 2015, humpback whale-watching activity in Bahía Málaga met only 16% of the conditions for sustainable governance, and it was characterized by unevenness in connections with markets (i.e. price variability and connections with intermediaries), income inequality, the lack of a whalewatching operators' association, and the lack of support from government organizations (Soto-Cortés et al, 2021). Therefore, we encourage the environmental authorities and local people to facilitate the formation of an association.…”
Section: Social Aspectsmentioning
confidence: 99%
“…Besides, knowledge on whale-watching tourism in Colombia is scarce, as there are currently only a few studies (e.g. Avila et al, 2015;Zapetis et al, 2017;Soto-Cortés et al, 2021). Therefore, the purpose of this research was to evaluate the current state of whale watching in Málaga NNP, how it has changed in time, evaluate the levels of compliance with whale-watching recommendations and identify challenges for the conservation of whales.…”
Section: Introductionmentioning
confidence: 99%
“…The sustainability of whale-watching tourism is currently limited by several factors, including poor implementation of scientific recommendations and ineffective communication about the negative impacts of these activities on fauna [25]. There is a wide consensus that a lack of best practices implementation and improper management can impact cetaceans and disrupt tourist experiences [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%